The Clinical Cases of Geleophysic Dysplasia: One Gene, Different Phenotypes - Evgenia Globa; Nataliya Zelinska; Andrew Dauber (Case Reports in Endocrinology)
Background. Geleophysic dysplasia is a rare multisystem disorder that principally affects the bones, joints, heart, and skin. This condition is inherited either in an autosomal dominant pattern due to FBN1 mutations or in an autosomal recessive pattern due to ADAMTSL2 mutations. Two patients with unaffected parents from unrelated families presented to their endocrinologist with severe short stature, resistant to growth hormone treatment. Routine endocrine tests did not reveal an underlying etiology. Exome sequencing was performed in each family. Our two patients, harboring de novo heterozygous FBN1 mutations p.Tyr1696Asp and p.Cys1748Ser, had common clinical symptoms such as severe short stature, characteristic facial features, short hands and feet, and limitation of joint movement. However, one patient had severe cardiac involvement whereas the other patient had tracheal stenosis requiring tracheostomy placement. Conclusions. Patients with severe dwarfism, skeletal anomalies, and other specific syndromic features (e.g., tracheal stenosis and cardiac valvulopathy) should undergo genetic testing to exclude acromelic dysplasia syndromes.